Evaluation of the Implementation of Article 23 Income Tax at PT. Taspen (Persero) Manado Branch Office - KAPARANG, Alann Sterry; RUNTU, Treesje; WEKU, Priscillia (PT Keberlanjutan Strategis Indonesia, 2023)
Income tax is important for the state because it is one of the largest revenues in the State Revenue and Expenditure Budget (APBN). Income tax article 23 is imposed on income derived from capital, service delivery, or gifts and awards, other than those that have been deducted with Article 21 income tax. Almost every company carries out rental activities from other parties for certain things that are needed to support its operational activities. and the service rental is the object of article 23 income tax. This study aims to determine the suitability between the application of calculation, deduction, deposit, and reporting of income tax article 23 at PT Taspen (Persero) Manado Branch Office with the applicable tax provisions. The type of research used is descriptive qualitative research with the aim of describing in writing the data obtained from interviews and documentation. The results obtained indicate that PT Taspen (Persero) Manado Branch Office has carried out tax obligations in terms of calculating, withholding, depositing and reporting income tax article 23 in accordance with applicable tax provisions.